Lemon Flavonoid Extract Eriomin Improves Pro/Antioxidant Status and Interferes with Cholesterol Metabolism without Affecting Serum Cholesterol Levels in Aged Rats - Šošić-Jurjević, Branka; Borković-Mitić, Slavica; Pavlović, Slađan; Vlahović, Dragana; Miler, Marko; Cesar, Thais [UNESP]; Ajdžanović, Vladimir; Milenkovic, Dragan; Stellaard, Frans; Trifunović, Svetlana; Filipović, Branko; Lütjohann, Dieter (MDPI, 2024)
This study aimed to assess the antioxidant capacity of lemon flavonoid extract Eriomin® (LE) and its impact on cholesterol metabolism in the context of healthy aging. We orally treated 24-month-old male Wistar rats with an LE (40 mg/kg) suspended in 0.3 mL of sunflower oil. At the same time, control groups received an equal volume of sunflower oil (CON) or remained untreated (ICON) daily for 4 weeks. We examined LE’s effects on superoxide dismutase and catalase- and glutathione-related enzyme activities, the concentration of lipid peroxides and protein carbonyls, total oxidant status (TOS) and antioxidant status (TAS), and oxidative stress index (OSI) in the liver, jejunum, and ileum. We also measured total cholesterol, its biosynthetic precursors (lanosterol, lathosterol, desmosterol), its degradation products (bile acid precursors) in the serum, liver, jejunum, and ileum, and serum phytosterols (intestinal absorption markers). LE reduced TOS, TAS, and OSI (p < 0.05) compared with control values, indicating its consistent antioxidant action in all examined organs. LE lowered hepatic desmosterol (p < 0.05) while also reducing 7α- and 24-hydroxycholesterol levels in the liver and ileum (p < 0.01). Serum cholesterol, hepatic gene expression, and the immunostaining intensity of CYP7A1 were unchanged. In conclusion, LE exerted non-enzymatic antioxidant effects and reduced cholesterol degradation, reducing its biosynthesis products, thereby maintaining serum cholesterol levels.
Keywords: 7α-hydroxycholesterol; aging; cholesterol; CYP7A1; desmosterol; Eriomin; lemon flavonoids; liver; oxidative stress; rat